2019
DOI: 10.1002/smll.201902534
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Determination of Carrier Density and Mobility in Working Organic Electrochemical Transistors

Abstract: voltages. For this reason, these devices have entered successfully the fields of biosensors and bioelectronics, unfolding their innovative potential in biomolecules detection, [2][3][4][5] electrophysiology, [6][7][8] in vitro and in vivo cellular recordings. [9][10][11] Currently, intensive research effort is focused on novel OECT channel materials [12] and architectures [13] to gain faster response time, increased sensitivity, and lower power consumption targeting new applications in wearable technology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
3
14
0
1
Order By: Relevance
“…agreement with a recent study of Mariani et al 24 , who used scanning electrochemical microscopy to determine the electrochemical potential in the OECT channel. In this microscopic study, a linear dependency of the electrochemical potential inside the channel is found, with abrupt potential changes at the source and drain contacts.…”
Section: Sourcesupporting
confidence: 91%
“…agreement with a recent study of Mariani et al 24 , who used scanning electrochemical microscopy to determine the electrochemical potential in the OECT channel. In this microscopic study, a linear dependency of the electrochemical potential inside the channel is found, with abrupt potential changes at the source and drain contacts.…”
Section: Sourcesupporting
confidence: 91%
“…Typically values measured in OECTs are on the order of 1-10 cm 2 V -1 s -1 . [10][11][12][13][14][15] In general, high mobilities for transport in OECT are reasonable, as the mobility is extracted in the high carrier density regime, were carrier trapping at band-edge states has only limited importance. At the same time, the accumulation does not exceed a critical limit at which energetic and structural disorder set-in due to PEDOT overoxidation.…”
Section: Resultsmentioning
confidence: 99%
“…[8] At the same time, the mixed conductivity renders the experimental characterization of individual ionic or electronic carrier mobilities difficult as both processes are intrinsically entangled and both can lead to the screening of electric fields or introduce local contact resistances. [9,10] Progress on all fronts is predicated on an advance in understanding the interrelations between ionic transport, electronic transport and ionic-electronic coupling and their dependence on processing, synthetic structure, microstructure/morphology, and electrolyte choice. [11] The extraction of the charge carrier mobility is crucial for the analysis of the transport properties of OMIECs.…”
mentioning
confidence: 99%
“…[ 18 ] However, this technique does not provide relevant information when applied to organic semiconductors in which ion uptake does not take place, as in most EGOFETs. Finally, microscale local potential measurements by scanning electrochemical microscopy have been demonstrated also on OECTs, [ 19 ] but they are based on the good conducting properties of OECTs, which are not generally met in EGOFETs.…”
Section: Introductionmentioning
confidence: 99%